(3GdGNJjGQ dJYdjd GdeNJGQs - (3CHh GdaVd GdehUdj, YHO Gddg Hf eMehO Hf ehOhO,s 599-683 (3g`(B.s (2002)
(3jJfGhd GdcJGH abg GdSfI(B.s
(3aj (B: (3GdGNJjGQ dJYdjd GdeNJGQ(B. -(3W(B. 1. -(3HjQhJ (B: (3GdecJHI GdYUQjI, (B2002. -(3eL(B. 5 (3aj (B1.s
Keywords: (3Gdabg GdMfajs